(untitled) (UNED Research Journal, 2014)
ABSTRACT: Pigeon pea (Cajanus cajan) is known for its ability to fix Nitrogen into the soil, to protect water basins and for its high nutritional value. In Costa Rica the legume is cultivated in San Carlos by a small association of pigeon pea, root and tuber farmers. With the objective of supporting marketing efforts, we used a focus group to test a salad made from pigeon pea and other. The salad was evaluated by ten consumers regarding market tendencies, competitors, ingredients, taste, packaging material, appearance and commercial opportunities. The product was highly accepted and described by the consumers as versatile and the trends in which it can be found in the market were pleasure, health and convenience. They preferred biodegradable packaging material with nutritional facts label. Its long shelf life compared to other salads is an asset, even if it is more expensive than competing salads. The acceptance of the product suggests its possibility of success and the importance of studying other aspects. KEY WORDS: Pigeon pea, focus group, salads, market, sensorial descriptors